Immunomodulatory activities of fractions from hot aqueous extract of wood from Clausena excavata - Manosroi A. (2014)
The effects of fractions from hot aqueous extract, acetone extract and the folklore preparation of Clausena excavata were studied on mouse splenocyte proliferation. The fractions of hot aqueous and acetone extracts were found to be the most active. On the contrary, the fractions from the crude folklore preparation resulted less active. This result could partly explain the popularity of this plant in folk medicine as a remedy for cancer and HIV patients in the eastern part of Thailand. © 2004 Elsevier B.V. All rights reserved.